Clinical and Electroencephalographic Features of the Seizures in Neuronal Surface Antibody-Associated Autoimmune Encephalitis - Wang, Yan; Yu, Yi; Hu, Yaping; Li, Ying; Song, Fan; Wang, Ying (Frontiers in Neurology, 2020)
Objectives: To investigate clinical and electroencephalographic features of the seizures in different types of neuronal surface antibody(NSAb) associated autoimmune encephalitis(AE). Methods: The clinical data of the seizures were analyzed in 18 patients with NSAb associated AEs diagnosed in the First Affiliated Hospital of DaLian Medical University. Results: From May 2013 to April 2019, a total of 18 cases of NSAb associated AE were diagnosed, including 9 cases of leucine-rich glioma inactivated 1 protein(LGI1) antibody associated encephalitis, 7 cases of anti-N-methyl-D-aspartate receptor(NMDAR) encephalitis, and 2 cases of anti-γ-aminobutyric acid B receptor(GABABR) encephalitis. All 9 cases(100%) with LGI1 AE had seizures manifesting in 3 types: faciobranchial dystonia seizure(FBDS)(44.4%), mesial temporal lobe epilepsy(MTLE)-like seizure(66.7%), and focal to bilateral tonic–clonic seizure(FBTCS) (77.8%). Six of 9(66.7%) showed abnormal signal on hippocampus or basal ganglia in brain MRI. Five of 7 cases(71%) with anti-NMDAR encephalitis had seizures manifesting in 3 types: focal aware seizure(40%), focal-impaired awareness seizure(20%), generalized tonic-clonic seizure(GTCS)(100%), and status epilepticus(SE) (40%). Three of 7(42.8%) showed abnormalities in brain MRI. Both patients with anti-GABABR encephalitis had seizures manifesting in 2 types: GTCS and MTLE-like seizure, one with SE. One showed abnormal signal on left hippocampus in brain MRI. All patients(100%) with 3 types of AE had abnormalities in EEG, showing diffuse(4/18) or focal slow waves(14/18) in background, interictal(10/18) or ictal(6/18) epileptic discharges in the temporal or other regions, 2 patients with anti-NMDAR encephalitis showed delta activity or rhythm in frontotemporal region. All patients with seizures showed good response to immunotherapy except one with LGI1 AE. Conclusions: Most patients with NSAb associated AE had seizures, seizure types varied between different types of AE. In LGI1 AE hippocampus and basal ganglia were two main targets, the corresponding seizure type was MTLE-like seizure and FBDS respectively. Anti-NMDAR encephalitis had more generalized than focal seizures. Delta activity or rhythm in frontotemporal region in EEG was helpful for diagnosis. Anti-GABABR encephalitis was characterized by refractory seizures as initial symptom, mainly GTCS or MTLE-like seizure. Most seizures in NSAb associated AE showed good response to immunotherapy and antiepileptic drugs should be considered as add-on symptomatic treatment.